Bowel Urgency in Inflammatory Bowel Disease - Teodora SPATARU; Ana Maria BAICEANU; Remus POPESCU; Lucian NEGREANU (Modern Medicine)
Inflammatory bowel disease (IBD) significantly impacts the patient’s quality of life with chronic disabling symptoms such as diarrhea, abdominal pain, bowel urgency, weight loss, fatigue. Bowel urgency, the sudden or immediate need for a bowel movement, is distinct from increased stool frequency and its underlying mechanisms are multifactorial and may vary within and between patients being driven primarily by active inflammation. It is one of the most bothersome symptoms experienced by patients with ulcerative colitis, with substantial negative impacts on quality of life and psychosocial functioning. Bowel urgency is often not discussed by patients due to embarrassment, and it may not be addressed adequately by healthcare providers. In fact, patients may report bowel urgency even if they are considered in remission based on symptoms or endoscopic findings. Several patient’s reported outcomes tools have been developed to measure the impact of urgency on patients’ life. This article presents the main challenges related to integration of bowel urgency into current care of IBD patients and its impact on treatment choice and monitoring.